Donut bakesmart / Sahla Zahra Mohd Affandi - Sahla Zahra, Mohd Affandi (2022)
Subjects was incorporated on 05 January 2015 in Malaysia under the name Donut Bakesmart sdn.bhd. Donut bakesmart business includes wholesale and retailer of sundry goods and a private limited company and has been existed for 6 years. In addition, it also sells cake container items, paper bag and more. it is located in Kuala Terengganu.